Transformasi Spiritualitas Peserta Didik Sebagai Benteng Iman Kristen Di Tengah Tantangan Dunia Digital Di SMAN 6 Tangerang - Muharoma Chomsatul Farida; Yunisemyo Avaa; Jonathan S. Sabah; Artini Bitu Meja; Yusuf Tamonob; Jirna W. Neolaka; Damaris R. Dara; Dewa Ningrat; Aguana E. Marumbona (Vieka Wahana Semesta, 2025)
Abstract This community service program (PKM) aims to strengthen the spiritual formation of Christian students at SMAN 6 Tangerang as a defense of faith amid the challenges of the digital world. Rapid technological development has reshaped students’ behavior, value orientation, and spiritual awareness, creating both opportunities and threats. This study employed a descriptive–quantitative approach supported by simple qualitative methods to measure students’ internal spirituality and their resilience in navigating digital influences. Data from 64 respondents show that students’ spiritual transformation is at a high level, reflected in consistent spiritual discipline, moral integrity, and personal commitment to Christian values. Furthermore, students demonstrated strong digital spiritual literacy, including self-control, critical evaluation of online content, and the use of digital platforms for spiritual growth. The findings indicate that the PKM program has a significant impact on strengthening students’ faith formation, enabling them to face digital temptations responsibly while maintaining their Christian identity. The study concludes that continuous and contextual spiritual formation integrated with digital literacy is essential to equip students as resilient Christian individuals capable of standing firm in their faith in the digital era. Abstrak Program Pengabdian kepada Masyarakat (PKM) ini bertujuan untuk memperkuat pembinaan spiritualitas peserta didik Kristen di SMAN 6 Tangerang sebagai benteng iman dalam menghadapi tantangan dunia digital. Perkembangan teknologi yang pesat telah membentuk pola pikir, perilaku, dan kesadaran spiritual peserta didik sehingga memunculkan peluang sekaligus ancaman. Penelitian ini menggunakan pendekatan deskriptif-kuantitatif yang dipadukan dengan metode kualitatif sederhana untuk mengukur spiritualitas internal peserta didik serta ketahanan iman mereka terhadap pengaruh digital. Berdasarkan data dari 64 responden, ditemukan bahwa tingkat transformasi spiritualitas berada pada kategori tinggi, ditandai dengan komitmen rohani, disiplin iman, dan integritas moral yang baik. Selain itu, peserta didik juga menunjukkan literasi digital rohani yang kuat, seperti kemampuan mengendalikan diri, memfilter konten negatif, serta memanfaatkan teknologi untuk pertumbuhan iman. Temuan ini menunjukkan bahwa program PKM memberikan dampak signifikan dalam memperkuat fondasi iman peserta didik sehingga mereka mampu menghadapi tantangan digital dengan bijaksana. Oleh karena itu, pembinaan spiritual yang berkelanjutan dan terintegrasi dengan literasi digital menjadi penting untuk membentuk peserta didik Kristen yang tangguh serta mampu mempertahankan identitas iman di era digital.